Coping strategies of student leaders for S.Y. 2018-2019 of Pamantasan ng Lungsod ng Maynila - Perez, Bernelyn Ann. 4 0 16; 5 (2018)
ABSTRACT: The aim of the study is to identify the coping strategies used by the student leaders of Pamantasan ng Lungsod ng Maynila for the Academic Year 2018-2019. Consequently, the researcher tried to determine if there is a significant difference between coping strategies of female and male student leaders. 120 student leaders were chosen by purposive quota sampling. The COPE Inventory (Carver, Scheier, & Weintraub, 1989) was used to measure the coping strategies that the student leaders exhibit. The researcher used item means, standard deviation, t-test, t-stats and for the statistical analysis of the data. The study found out that Positive Reinterpretation and Growth , Planning and Active Coping are the three most used coping strategies while Substance Use, Behavioral Disengagement and Denial are the three least used coping strategies of student leaders. The study also found out that there is a significant difference between Focus on and Venting of Emotions, Religious Coping, Substance Use and Acceptance coping of the student leaders.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2